The Royal Navy’s Intervention at the Beginning of Chile’s Independence Process, 1810-1814 - Hardy Videla, David (Historia, 2024)
When Chile started its emancipation process from the Spanish empire (1810-1814), the Royal Navy was the only formal representation of the United Kingdom in South America’s west coast. During those years only two British warships arrived at Valparaíso. The analysis of the correspondence exchanged by Captain Charles Fleming and Commodore James Hillyar with the British, Spanish, and Chilean authorities reveals they were carrying out missions of a military and strategic nature, linked to the international conflicts in which England was engaged. However, both officers became directly involved in internal political affairs between Spain and its colonies, causing divergent effects among the opposing players. The examination of such correspondence allows identifying, in official sources from decision-making authorities, the initial British interests in that distant colony. This study argues that, even though the British governments favoured a balance of power and non-intervention policy towards the European powers, during the analysed period the Royal Navy’s actions in Chile reveals an erratic policy concerning Spain and its South American possessions. Even more, those events are evidence that the prevailing British geostrategic and security interests were beyond the economic and commercial benefits which British subjects were looking for in the emerging republic; and concludes that both naval officers interventions gave rise to the first perception of Great Britain’s future influence in Chile’s emancipation struggle, inspiring the mutual representation which would dominate the bilateral relation between British and Chilean authorities during the first decades of the nineteenth century.